2005
DOI: 10.1152/ajpgi.00025.2005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the human peptide transporter PEPT1 promoter: Sp1 functions as a basal transcriptional regulator of human PEPT1

Abstract: H+-coupled peptide transporter 1 (PEPT1, SLC15A1) localized at the brush-border membranes of intestinal epithelial cells plays an important role in the intestinal absorption of small peptides and a variety of peptidemimetic drugs. PEPT1 is regulated by various factors, including hormones, dietary conditions, some pharmaceutics, and diurnal rhythm. But there is little information about the transcriptional regulation of PEPT1. In the present study, therefore, we cloned the human (h)PEPT1 promoter region and exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
48
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 29 publications
2
48
0
Order By: Relevance
“…For example, CREB-binding protein CBP/p300 acts as a cofactor for transcriptional activation by CREB (43). The Cdx proteins are involved in the regulation of intestine-specific genes, such as sucrase-isomaltase, intestinal phospholipase A/lysophospholipase, lactase-phlorizin hydrolase, p21, claudin-2, and the iron transport protein hephaestin (2,7,26,32,43). Cdx2 itself appears to play critical roles in gut differentiation, proliferation, and neoplasia (44), and it was recently demonstrated that the gastric mucosa of transgenic Cdx2-overexpressing mice are morphologically changed to intestinal metaplastic mucosa, including microvilli, and PepT1 expression (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, CREB-binding protein CBP/p300 acts as a cofactor for transcriptional activation by CREB (43). The Cdx proteins are involved in the regulation of intestine-specific genes, such as sucrase-isomaltase, intestinal phospholipase A/lysophospholipase, lactase-phlorizin hydrolase, p21, claudin-2, and the iron transport protein hephaestin (2,7,26,32,43). Cdx2 itself appears to play critical roles in gut differentiation, proliferation, and neoplasia (44), and it was recently demonstrated that the gastric mucosa of transgenic Cdx2-overexpressing mice are morphologically changed to intestinal metaplastic mucosa, including microvilli, and PepT1 expression (44).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we previously demonstrated that short term leptin treatment increased hPepT1 activity in vivo and in vitro (26). The 5Ј-flanking region of the hPepT1 gene has been cloned, and investigations into the regulation of its transcription have indicated that the Sp1 transcription factor functions in basal transcriptional regulation of hPepT1 (32). However, no previous study has investigated transcriptional regulation of hPepT1 in response to hormones, particularly during intestinal inflammation.…”
mentioning
confidence: 99%
“…These transcription factors then translocate into the nucleus and activate the transcription of a number of target genes (Morton et al, 1998), among which the PepT1 gene could be a candidate. The promoter regions of the rat, mouse and human PepT1 gene (Shiraga et al, 1999;Fei et al, 2000;Shimakura et al, 2005) have been characterized, and they contain a number of potential binding sites for regulatory factors of gene transcription that can be targeted by leptin signaling pathways. Likewise, Nduati et al (2007) showed that cAMP response element-binding protein (CREB) and caudal-related homeobox 2 (Cdx2) are involved in PepT1 regulation by leptin in vitro.…”
mentioning
confidence: 99%
“…Nuclear extract was prepared from OK cells according to the method of Shimakura et al (2005). The double-stranded oligonucleotides used in the EMSA are listed in Table 1.…”
mentioning
confidence: 99%